ChemInform Abstract: Hydrothermal Synthesis, Structure Investigation, and Oxide Ion Conductivity of Mixed Si/Ge‐Based Apatite‐Type Phases. Issue 29 (22nd July 2014) - Li, Henan; Baikie, Tom; Pramana, Stevin S.; Shin, J. Felix; Keenan, Philip J.; Slater, Peter R.; Brink, Frank; Hester, James; An, Tao; White, Tim J.
Abstract Mixed Si/Ge‐based single phase apatites ([AI4][AII6] [(BO4)6]O2) of the formula La9.33□0.67Si6‐xGex O26 (□: vacancy; 0 ≤ x ≤ 6) are prepared by mild hydrothermal synthesis from La2O3/(SiO2 + GeO2)/Na2O/H2O gels (autoclave, 180—240 °C).